The effect of chemical treatment and temperature on some rheological properties of Pinus radiata - Van Zyl, J. D.(Johannes Daniel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1971.